Matriculation in U.S. Economics Ph.D. Programs: How Many Accepted Americans Do Not Enroll? - Finegan, T. Aldrich; Stock, Wendy A; Siegfried, John J (American Economic Review, 2006)
Matriculation in U.S. Economics Ph.D. Programs: How Many Accepted Americans Do Not Enroll? by T. Aldrich Finegan, Wendy A. Stock and John J. Siegfried. Published in volume 96, issue 2, pages 453-457 of American Economic Review, May 2006